Evolution of microstructure and crystallographic texture of Ni-Mn-Ga melt-spun ribbons exhibiting 1.15% magnetic field-induced strain. (15th October 2021) - Wójcik, Anna; Chulist, Robert; Czaja, Paweł; Kowalczyk, Maciej; Zackiewicz, Przemysław; Schell, Norbert; Maziarz, Wojciech
Abstract: The microstructure and texture evolution of 10M Ni-Mn-Ga melt-spun ribbons were thoroughly evaluated by high-energy synchrotron radiation and electron backscatter diffraction. The as-spun ribbons were subjected to annealing treatment in order to tailor microstructure, atomic order degree, and crystallographic texture. The optimum annealing treatment at 1173 K for 72 h produced a homogenous <100> fiber texture and induced grain growth to the size that spans the entire ribbon thickness. This in turn reduced microstructural constraints for twin variant reorientation in the direction perpendicular to the ribbon surface. On the other hand, a homogenous radial microstructure ensured in-plane stress/strain compatibility giving rise to strain accommodation during variant reorientation. Particular attention was also given to the evaluation of atomic order, which to the largest extent controls the characteristic transformation temperatures. It also lowered the twinning stress to a level sufficiently low for martensitic variant reorientation under magnetic field. As a result, 1.15% magnetic field-induced strain without the aid of mechanical training in the self-accommodated state was achieved. Grapihcal abstract: Image, graphical abstract